Alterations in gut microbiota and urine metabolomics in infants with yin-deficiency constitution aged 0–2 years. Issue 4 (April 2023) - Zhao, Haihong; Ren, Qiqi; Wang, Huai-yu; Zong, Yuhan; Zhao, Weibo; Wang, Yaqi; Qu, Miao; Wang, Ji
Abstract: Background: Based on the constitution theroy, infants are classified into balanced constitution (BC) and unbalanced constitution. Yin-deficiency constitution (YINDC) is a common type of unbalanced constitutions in Chinese infants. An infant's gut microbiota directly affects the child's health and has long-term effects on the maturation of the immune and endocrine systems throughout life. However, the gut microbiota of infants with YINDC remains unknown. Herein, we aimed to evaluate the intestinal flora profiles and urinary metabolites in infant with YINDC, find biomarkers to identify YINDC, and promote our understanding of infant constitution classification. Methods: Constitutional Medicine Questionnaires were used to assess the infants' constitution types. 47 infants with 21 cases of YINDC and 26 cases of BC were included, and a cross-sectional sampling of stool and urine was conducted. Fecal microbiota was characterized using 16S rRNA sequencing, and urinary metabolomics was profiled using UPLC-Q-TOF/MS method. YINDC markers with high accuracy were identified using receiver operating characteristic (ROC) analysis. Results: The diversity and composition of intestinal flora and urinary metabolites differed significantly between the YINDC and BC groups. A total of 13 obviously different genera and 55 altered metabolites were identified. Stool microbiome shifts were associated with urine metabolite changes. A combined marker comprising two genera may have a high potential to identify YINDC with an AUC of 0.845. Conclusions: Infants with YINDC had a unique gut microbiota and metabolomic profile resulting in a constitutional microclassification. The altered gut microbiome in YINDC may account for the higher risk of cardiovascular diseases. Metabolomic analysis of urine showed that metabolic pathways, including histidine metabolism, proximal tubule bicarbonate reclamation, arginine biosynthesis, and steroid hormone biosynthesis, were altered in infants with YINDC. Additionally, the combined bacterial biomarker had the ability to identify YINDC. Identifying YINDC in infancy and intervening at an early stage is crucial for preventing cardiovascular diseases.